Analisis Karakteristik Nilai Religius Dan Makna Spiritual Pada Novel Negeri 5 Menara - Aida Fitri Puspitasari; Fajarotul Nur Isnaini; Renie Ria Rusmawati (PT. Nawa Edukasi Nusantara, 2025)
This study examines religious values and spiritual meaning in the novel Negeri 5 Menara by Ahmad Fuadi. The story portrays life in a pesantren, highlighting Islamic values such as the spirit of learning, prayer, and faith in Allah's will. Using a qualitative approach, the study analyzes religious elements in the plot, characters, and conflicts. It also explores the spiritual motivations driving the characters to achieve their goals, guided by the principle